FAME 2: FFR—Guided PCI Reduces Urgent Revascularization - Hoyle, Brian (MD Conference Express, 2014)
This article presents updated trial data that demonstrated that fractional flow reserve (FFR)-guided percutaneous coronary intervention (PCI) reduces cardiovascular events when compared to medical therapy in patients with stable coronary artery disease (CAD). The Fractional Flow Reserve-Guided Percutaneous Coronary Intervention Plus Optimal Medical Treatment (OMT) Versus OMT trial [FAME 2; De Bruyne B et al. N Engl J Med. 2014] was undertaken to determine if FFR-guided PCI improves outcomes in patients with stable CAD.